2009
DOI: 10.1021/ma902323t
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Temperature-Induced Subdiffusion of Water on the Micrometer Scale in a Nafion Membrane

Abstract: To investigate the topological features of proton transport in perfluorosulfonic membranes, we performed time-dependent (t)H NMR pulsed gradient spin-echo experiments on four samples of Nafion-115 with lambda = 0.5, 3.2, 5.8, and 12.4 water molecules per sulfonic group at different temperatures ranging from 278 to 348 K. A subdiffusive behavior of water, < z(2) > = 2D(alpha)t(alpha) with 0.75 < alpha < 1, was observed above 320 K for each of the four samples. The onset of water subdiffusion with increasing tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…The PFSA/SiO 2 membrane with 3 wt% concentration in silica shows a change in the values of E a in the low-temperature range in synchrony with the changes in the value of diffusivities measured at 50 ° C (see Figure 2 a). The above results are in agreement with that of Casieri et al [ 14 ] They observed a subdiffusive behavior for Nafi on-115 membranes above 320 K, and in this case, the mean-square displacement is given by 〈 z 2 〉 = 2 D α Δ α with α ∈ [0.75, 1]. The interpretation of the water subdiffusive process was related to the fact that the connectivity of water channels starts to decrease when the membrane temperature increases.…”
Section: Temperature Dependence Of Diffusivity and Kurtosissupporting
confidence: 91%
See 4 more Smart Citations
“…The PFSA/SiO 2 membrane with 3 wt% concentration in silica shows a change in the values of E a in the low-temperature range in synchrony with the changes in the value of diffusivities measured at 50 ° C (see Figure 2 a). The above results are in agreement with that of Casieri et al [ 14 ] They observed a subdiffusive behavior for Nafi on-115 membranes above 320 K, and in this case, the mean-square displacement is given by 〈 z 2 〉 = 2 D α Δ α with α ∈ [0.75, 1]. The interpretation of the water subdiffusive process was related to the fact that the connectivity of water channels starts to decrease when the membrane temperature increases.…”
Section: Temperature Dependence Of Diffusivity and Kurtosissupporting
confidence: 91%
“…[ 10 ] Water channels described by this model are surrounded by partially hydrophilic side branches, forming inverted-micelle cylinders. Furthermore, water diffusion coeffi cient NMR spectroscopy measurements [12][13][14] and ionic conductivity experiments [ 15 ] showed the existence of coherent orientation of aqueous pathways in Nafi on membrane. Furthermore, the anisotropy of channel alignment in different Nafi on membranes was measured using the splitting of 2 H wideline NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations